Inspired speech : prophecy in the ancient Near East : essays in honor of Herbert B. Huffmon - Huffmon, H. B. (Herbert Bardwell); Kaltner, John, 1954-; Stulman, Louis, 1953- (Journal for the study of the Old Testament. Supplement series, 2004)
Inspired Speech was originally published as a Festschrift to honor the work of Professor Herbert B. Huffmon, Professor of Old Testament/Hebrew Bible at Drew University. Thirty-three of his colleagues and students contributed to the work, which explores various aspects of prophecy in ancient Israel and its neighboring cultures. The result is a volume which provides an excellent overview of the current state and future directions of scholarship on prophecy in the biblical world. Contributors: Suzanne Richard, Frank Moore Cross, George E. Mendenhall, Martti Nissinen, Robert R. Wilson, Mary Chilto.